The Dolicholatiridae and Fasciolariidae (Gastropoda, Buccinoidea) of the Miocene Paratethys Sea - Harzhauser, Mathias; Landau, Bernard M.; Vermeij, Geerat J. (Zootaxa, 2024)
We describe one species of Dolicholatiridae and 30 species of Fasciolariidae from the Miocene of the Central Paratethys Sea. The first records of the family Dolicholatiridae and of the Fasciolariidae genus Takashius are documented from the Neogene of Europe, and we describe a first Miocene radiation of the extant Mediterranean Fusininae Pseudofusus. The Dolicholatiridae Dulaiania nov. gen. and the Fasciolariidae Cryptoneolatirus nov. gen., Eurolatirus nov. gen., Fraudifusinus nov. gen., Snyderifusus nov. gen. and Xenofusinus nov. gen. are described as new genera. Fraudifusinus grundensis nov. sp., Fraudifusinus pseudocrispoides nov. sp., Pseudofusus balteus nov. sp., Pseudofusus rostratoides nov. sp., Pseudofusus stahlschmidti nov. sp., Pseudofusus? schuberthi nov. sp., Takashius kantori nov. sp. and Takashius vinculum nov. sp. are introduced as new species. Neotypes are designated for Angustifusus hoessii (Naumann, 1852) and Pseudolatirus bilineatus (Naumann, 1852). Lectotypes are designated for Angustifusus vindobonensis (Hoernes & Auinger, 1890), Fraudifusinus crispoides (Kittl, 1887), Tarantinaea hoernesii (Seguenza, 1875), Pseudofusus austriacus (Hoernes & Auinger, 1890), Snyderifusus prevosti (Hörnes, 1853), and Xenofusinus haueri (Hoernes, 1875). More than two thirds of the species are described as new combinations, illustrating the importance of taxonomic revisions for any paleobiogeographic and biostratigraphic analyses at the species and the genus levels. As a result, our revision led to a distinct decrease of species shared with adjacent regions, compared to previous data. The Tudiclidae Euthria reussi (Hoernes & Auinger, 1885) is discussed as addendum to Harzhauser & Lanau (2024).